Educational Knowledge: Games to stimulate growth in children among mothers of toddlers - Harsono Harsono; Rinayati Rinayati; Hargianti Dini Iswandari; Okti Trihastuti Dyah Retnaningrum (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Factors that help achieve child growth and development are proper stimulation. The role of parents, in this case, the mother has a big enough contribution to the successful process of child development. Purpose: To find out the increase in mothers of toddler knowledge about the benefits of games that stimulate children's growthMethod: The form of this research design is a pre-experimental design (One-Group Pretest-Posttest) with a purposive sampling technique and the research population is mothers of under five children in Gondoriyo Semarang. Processing techniques and analysis of quantitative data using the analysis of the t-test (test T). Results: The normality test, shows that the Sig value in the Shapiro-Wik column for the mother’s knowledge variable before and after being given an educational game is less than 0.05 so it is declared not to have a normal distribution. So to find out whether there is a difference in the average knowledge of mothers regarding educational games, an analysis of the Wilcoxon Signed test was carried out. Based on the results of the Wilcoxon signed test, it was found that the asymp sig (2-tailed) value was 0,000 < 0.05 so it can be concluded that there is a difference in the average knowledge of toddler mothers before and after being given educational games stimulating growth and development.Conclusion: Mother's knowledge increases about the benefits of providing educational games to stimulate child growth and development